PENGEMBANGAN VISUAL BRAND IDENTITY DE GROOMING SEBAGAI STRATEGI PENGEMBANGAN LAYANAN PET GROOMING - Jemima Katherine Lemuela; Edy Chandra (Universitas Trisakti, 2023)
Abstract Visual Development of De Grooming Brand Identity as a Pet Grooming Service Development Strategy. The development of ownership and maintenance of pets (pets) during the pandemic to the endemic period experienced a significant increase, especially the maintenance of cats and dogs. Most of the owners are office workers who have high activity. The amount of logistical needs for pets has increased from 2014 to 2021. Based on statistical data, the consumption volume of Pet Food Indonesia between 2014-2021 increased from 512.2 in 2014 to 942.2 in 2021. Apart from the statistical data, there are other factors that will encourage the emergence of new independent entrepreneurs or franchises in logistics and pet care services. Currently, one of the needs for pet care mobility services is a great opportunity for one of the Hi Pets micro, small and medium units (MSMEs) to develop additional mobility services for their prospective customers. The solution provided in this study is in the form of visual development using the linear design strategy method from Alina Wheeler. The result is a brand identity called De Grooming. Keywords: brand identity, mobile pet grooming, logo Abstrak Pengembangan Visual Brand Identity De Grooming Sebagai Strategi Pengembangan Layanan Pet Grooming. Perkembangan kepemilikan dan pemeliharaan terhadap hewan peliharaan (pet) semasa pandemi hingga masa endemi mengalami peningkatan yang cukup signifikan, terutama pemeliharaan terhadap hewan kucing dan anjing. Para pemiliknya sebagian besar adalah dari kalangan pekerja kantor yang memiliki aktivitas tinggi. Jumlah kebutuhan logistik untuk hewan peliharaan meningkat sejak tahun 2014 hingga tahun 2021. Berdasarkan data statistik volume konsumsi Pet Food Indonesia antara tahun 2014-2021 mengalami kenaikan pada nilai 512,2 pada tahun 2014 menjadi 942,2 di tahun 2021. Selain data statistik angka tersebut tentunya ada faktor lainnya yang akan mendorong munculnya para wirausaha baru secara mandiri atupun waralaba di bidang logistik dan pelayanan perawatan hewan peliharaan (pet). Saat ini salah satu kebutuhan akan layanan mobilitas perawatan pet menjadi peluang besar untuk salah satu unit mikro kecil menengah (UMKM) Hi Pets untuk mengembangkan tambahan layanan mobilitas bagi calon konsumennya. Solusi yang diberikan dalam penelitian ini adalah dalam bentuk pengembangan visual dengan menggunakan metode strategi perancangan linier dari Alina Wheeler. Hasilnya berupa brand identity yang diberi nama De Grooming. Kata kunci: brand identity, mobile pet grooming, logo